KEPRIYAYIAN DALAM KARYA SASTRA: Berkaca pada Para Priyayi, Karya Umar Kayam* - Lee Yeon (Jurnal Tuturan, 2012)
Priyayi are the members of a social group, which had great influence in Javanese society and dominated it for a long time. Their importance derives from the leading role they played in the modernization process and the fact that they formed the intellectual class of society, which had progressed without loosing their Javenese cultural identity and origins. Although the status of priyayi lost its power and shine after independence of Indonesia(1945), the influece of priyayi-especially their moral and ethics view-can be felt in Indonesian society up to the present day. In connection to that, this research is an attempt to understand the priyayi through the literature.